2019
DOI: 10.29007/gwn6
|View full text |Cite
|
Sign up to set email alerts
|

Move it or lose it: Exploring the relation of defensive disruptiveness and team success

Abstract: Introduction: Due to the increasing number of tracking data available for official matches in different leagues there are new ways to capture the performance of teams. To not rely on notational data, we previously introduced the D-Def (Goes et. al, 2018), an aggregated variable to quantify passing solely based on tracking data. This value captures the change of organisation by a pass (defensive disruptiveness). In this study, we updated the D-Def by including an automated classifier for subunits, instead of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This result supports the idea that D-Def can be used to evaluated passing performance. This is in line with earlier studies demonstrating that D-Def can differentiate between good and bad passers on an individual level [ 15 ], and D-Def being a better predictor of the end result of a game in comparison to other key performance indicators [ 18 ]. This connection of D-Def with the end result can now be expanded with the current finding of D-Def showing higher values in successful attacks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result supports the idea that D-Def can be used to evaluated passing performance. This is in line with earlier studies demonstrating that D-Def can differentiate between good and bad passers on an individual level [ 15 ], and D-Def being a better predictor of the end result of a game in comparison to other key performance indicators [ 18 ]. This connection of D-Def with the end result can now be expanded with the current finding of D-Def showing higher values in successful attacks.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, other studies showed a higher chance of scoring against an unbalanced defense compared to a balanced defense [ 16 , 17 ]. Earlier studies already revealed that D-Def can differentiate between good and bad passers on the individual level [ 15 ] and is a better predictor of the final result of a match compared to other performance indicators [ 18 ]. However, since the end result of a game is strongly influenced by chance [ 19 ], the relationship of D-Def and success should not solely be traced back to the end result.…”
Section: Introductionmentioning
confidence: 99%
“…For defenders, it only includes last 6 players on the field plus the goalkeeper based on the longitudinal coordinates or how many players are overplayed in terms of distance between the ball and the center of the opponent's goal. (Memmert et al, 2017), (Rein et al, 2017), (Goes et al, 2019), (Steiner et al, 2019) D-Def (measures the disturbance a pass causes on the defense) (Goes et al, 2018), (Kempe and Goes, 2019) I-Mov (the movement of all opposing players in response to a pass) (Goes et al, 2018), (Kempe…”
Section: Pass Evaluation Metricsmentioning
confidence: 99%
“…Furthermore, from a technical point of view, players are in ball possession 57 times and play 38 passes on average (Forcher et al, 2022d). Lastly, in a tactical context, studies revealed that passes with a higher potential of disrupting the opposing team lead to more successful attacks (Kempe and Goes, 2019;Forcher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%